SARS‐CoV‐2 innate effector associations and viral load in early nasopharyngeal infection. Issue 4 (24th February 2021) - Liou, Theodore G.; Adler, Frederick R.; Cahill, Barbara C.; Cox, David R.; Cox, James E.; Grant, Garett J.; Hanson, Kimberly E.; Hartsell, Stephen C.; Hatton, Nathan D.; Helms, My N.; Jensen, Judy L.; Kartsonaki, Christiana; et al.
Abstract: COVID‐19 causes severe disease with poor outcomes. We tested the hypothesis that early SARS‐CoV‐2 viral infection disrupts innate immune responses. These changes may be important for understanding subsequent clinical outcomes. We obtained residual nasopharyngeal swab samples from individuals who requested COVID‐19 testing for symptoms at drive‐through COVID‐19 clinical testing sites operated by the University of Utah. We applied multiplex immunoassays, real‐time polymerase chain reaction assays and quantitative proteomics to 20 virus‐positive and 20 virus‐negative samples. ACE ‐ 2 transcripts increased with infection (OR =17.4, 95% CI [CI] =4.78–63.8) and increasing viral N1 protein transcript load (OR =1.16, CI =1.10–1.23). Transcripts for two interferons (IFN) were elevated, IFN ‐ λ1 (OR =71, CI =7.07–713) and IFN ‐ λ2 (OR =40.2, CI =3.86–419), and closely associated with viral N1 transcripts (OR =1.35, CI =1.23–1.49 and OR =1.33 CI =1.20–1.47, respectively). Only transcripts for IP ‐ 10 were increased among systemic inflammatory cytokines that we examined (OR =131, CI =1 .01–2620). We found widespread discrepancies between transcription and translation. IFN proteins were unchanged or decreased in infected samples (IFN‐γ OR =0.90 CI =0.33–0.79, IFN‐λ2, 3 OR =0.60 CI =0.48–0.74) suggesting viral‐induced shut‐off of host antiviral protein responses. However, proteins for IP ‐ 10 (OR =3.74 CI =2.07–6.77) and several interferon‐stimulated genes (ISG) increased with viral load ( BST ‐ 1 OR =25.1, CI =3.33–188; IFIT1 OR =19.5, CI =4.25–89.2; IFIT3 OR =245, CI =15–4020; MX ‐ 1 OR =3.33, CI =1.44–7.70). Older age was associated with substantial modifications of some effects. Ambulatory symptomatic patients had an innate immune response with SARS‐CoV‐2 infection characterized by elevated IFN, proinflammatory cytokine and ISG transcripts, but there is evidence of a viral‐induced host shut‐off of antiviral responses. Our findings may characterize the disrupted immune landscape common in patients with early disease. Abstract : SARS‐CoV‐2 disrupts the innate immune landscape. Interferon‐lambda transcripts are increased but protein production may be blocked by viral shut‐off. However, key interferon‐stimulated antiviral genes are transcribed and translated.